Etnobotánica de las plantas medicinales empleadas en el área rural de la parroquia San Carlos, cantón Quevedo, Los Ríos, Ecuador - Zambrano Intriago, Leonardo Fabián (2014)
There is currently great interest in the use of medicinal plants, enriching knowledge of the residents of the communities of our country on the use of the same, for different diseases affecting humans. The purpose of this work focuses on detail and determine the importance of medicinal plants in rural areas of the parish San Carlos. From November 2013 until May 2014 an investigation was conducted with the purpose of studying ethnobotanical species and how they are used by people in San Carlos, Quevedo, Los Rios. 50 semi-estructured surveys where done for this. For the data analysis, there used 4 important principles: medicinal plants relative importance (IRE), that served to identify the value of the information (IVUis), to determine the species use and value (UVS), (RUV) to demonstrate the importance of the investigation fields most representative plants. Information of 48 medicinal plants was lifted 43 plants botanical information was extracted. As for the other un-identified 5, they were used in the results of the research, with its name and medicinal use. The reported plants were distributed into 30 families and 4 genders. The families with the most medicinal value were Lamiaceae, Asteraceae y Apiaceae. The other families did not represent a relevant result. The most used parts in the making of the medicine were the leaves (76.7%), the main preparation method was the infusion (83.7%) and the most employed consume way was drinking, with results of (86.0%). The most relevant plants in terms of medicinal purpose in San Carlos were the (Cymbopogon citratus (D.C). Staff.) the (Origanum vulgare L.) and the (Mentha sativa L.).